2014
DOI: 10.1089/ten.tec.2013.0286
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Derived Polymer/Extracellular Matrix Composite Scaffolds for Cartilage Regeneration, Part 1: Investigation of Cocultures and Seeding Densities for Improved Extracellular Matrix Deposition

Abstract: This study investigated the coculture of chondrocytes and mesenchymal stem cells (MSCs) on electrospun fibrous polymer scaffolds to produce polymer/extracellular matrix (ECM) hybrid constructs with the objective of reducing the number of chondrocytes necessary to produce ample cartilage-like ECM within the scaffolds. To generate these hybrid constructs, electrospun poly(e-caprolactone) fibrous scaffolds were seeded at both high and low initial densities with five different ratios of chondrocytes to MSCs: 1:0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 58 publications
1
47
1
Order By: Relevance
“…Non-woven fibrous poly(∊ -caprolactone) (PCL) scaffolds were fabricated by electrospinning using previously described methods [15]. 18% (w/w) PCL was first dissolved in a 5:1 (v/v) solution of chloroform: methanol and expelled at a flowrate of 25 mL/hr into an electric field formed by a voltage source with 30 kV applied voltage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-woven fibrous poly(∊ -caprolactone) (PCL) scaffolds were fabricated by electrospinning using previously described methods [15]. 18% (w/w) PCL was first dissolved in a 5:1 (v/v) solution of chloroform: methanol and expelled at a flowrate of 25 mL/hr into an electric field formed by a voltage source with 30 kV applied voltage.…”
Section: Methodsmentioning
confidence: 99%
“…One such method is by utilizing co-cultures of chondrocytes and MSCs to generate similar quantities of cartilage-like ECM as cultures of chondrocytes alone [15, 16]. Various studies have shown that co-culturing MSCs with chondrocytes leads to increased chondrogenic gene expression and ECM deposition when cultured both in direct cell-cell contact or separated by a barrier, such as a Transwell® membrane, or in conditioned media systems [17-21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires the polymer to have functionalizable pendant chains or end groups [29]. A less common, but increasingly investigated approach is to use cells to deposit their native ECM onto the scaffold, followed by decellularization and the use of this ECM-polymer composite scaffold as a bioactive support for subsequent recellularization [33,34,35]. This approach (which we refer to as the cellularization-decell-recell cycle) harnesses the naturally-occurring bioactive signals from a selected cell source to modify the biological responses of subsequently seeded cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the ECM determines tissue functionality. Recent tissue engineering strategies have focused on mimicking the composition of the ECM to achieve desired cellular behavior and lineage specific differentiation to facilitate regeneration of tissues such as bone, dental pulp and cartilage (25). The primary reason behind such approaches lies in the complex nature of the ECM.…”
Section: Introductionmentioning
confidence: 99%